Descartes on the Animal Within, and the Animals Without. Issue 8 (7th November 2020) - Thomas, Evan
Abstract: Descartes held that animals are material automata without minds. However, this raises a puzzle. Descartes's argument for this doctrine relies on the claims that animals lack language and general intelligence. But these claims seem compatible with the view that animals have minds. As a solution to this puzzle, I defend what I call the introspective-analogical interpretation. According to this interpretation, Descartes employs introspection to show that certain human behaviors do not depend on thought but rather on automatic bodily processes. Descartes then argues that animal behavior resembles only those behaviors that are automatic in humans. Analogy thus supports the view that the behaviors of animals do not depend on thought but are, rather, automatic. And if animal behavior is automatic, then animals are best regarded as automata.